DINAMIKA KREDIT PROGRAM DAN PERSPEKTIF SKEMA BARU KREDIT USAHA RAKYAT UNTUK PEMBIAYAAN PERTANIAN 2020-2024 - Sri Wahyuni; Endro Gunawan; Sri Hastuti Suhartini; Julia Forcina Sinuraya; Mat Syukur; Nyak Ilham (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2020)
One of the Government's efforts to achieve food security is through increasing People’s Business Credit (KUR) fund. KUR disbursement, so far, is relatively low and it is necessary to implement the new scheme perspective on KUR. This paper presents the new scheme perspective on KUR to improve its disbursement as well as agricultural production. The basis for the new scheme perspective is derived from Agricultural Financing Program review, KUR implementation, driving factors and the benefits. Agricultural Financing Program before and during KUR era shows that the success of KUR disbursement is affected by socialization and human resources capacity. This finding is supported by the review that KUR disbursement success is determined by human’s character. Existing KUR scheme gets better and successful in increasing the farmers’ income. On the other hand, some unsuccessful results ok KUR is due to moral hazard. The new scheme of KUR should focus on effective and efficient socialization of this program credit to all stakeholders. For example, socialization is implemented using social media which is easily understood and accessed. Utilizing applications of cellular phone is also very useful to improve the program knowledge and to deal with moral hazard. Additionally, it is necessary to include ecological aspect as well as youth and women access in the scheme.